a: \(\Leftrightarrow x^2-6x-16-x^2+6x-9=2\)
=>-25=2(loại)
b: \(\Leftrightarrow x^2-25-x^2-x=x-3\)
=>-x-25=x-3
=>-2x=22
=>x=-11
c: =>(x+4+x-3)(x+4-x+3)=0
=>2x+1=0
=>x=-1/2
a: \(\Leftrightarrow x^2-6x-16-x^2+6x-9=2\)
=>-25=2(loại)
b: \(\Leftrightarrow x^2-25-x^2-x=x-3\)
=>-x-25=x-3
=>-2x=22
=>x=-11
c: =>(x+4+x-3)(x+4-x+3)=0
=>2x+1=0
=>x=-1/2
tìm x biết:
a) x - 3= (3 - x)^2
b) x^3 + 3/2x^2 + 3/4x + 1/8 = 1/64
c) 8x^3 - 50x = 0
d) (x - 2) (x^2 + 2x + 7) + 2(x^2 - 4) - 5(x - 2) = 0
e) x(x + 3) - x^2 - 3x = 0
f) x^3 + 27 + (x + 3) (x - 9) = 0
Giúp mik vs ạ
Bài 1:Tìm x biết:
a.,2x(x-3)-15+5x=0
b,x^3-7x
c,(2x-3)^2-(x+5)^2=0
d,x^3-x^2-4x^2+8x-4=0
giúp mk với mk cầm gấp lắm TvT
Bài 4: Tìm x, biết:
a) 3(2x – 3) + 2(2 – x) = –3 ; b) x(5 – 2x) + 2x(x – 1) = 13 ;
c) 5x(x – 1) – (x + 2)(5x – 7) = 6 ; d) 3x(2x + 3) – (2x + 5)(3x – 2) = 8 ;
e) 2(5x – 8) – 3(4x – 5) = 4(3x – 4) + 11; f) 2x(6x – 2x 2 ) + 3x 2 (x – 4) = 8.
Tìm x biết:
a, 16x² – 9(x + 1)²= 0
b, x2 (x – 1) – 4x2 + 8x – 4 = 0
c, x(2x – 3) – 2(3 – 2x) = 0
d, (x – 3)(x² + 3x + 9) – x(x + 2)(x – 2) = 1
e, 4x² + 4x – 6 = 2
f, 2x² + 7x + 3 = 0
. Tìm x, biết:
a) 6x.(x – 5) + 3x.(7 – 2x) = 18 b) 2x.(3x + 1) + (4 – 2x).3x = 7 c) 0,5x.(0,4 – 4x) + (2x + 5).x = -6,5 | d) (x + 3)(x + 2) – (x - 2)(x + 5) = 6 e) 3(2x - 1)(3x - 1) – (2x - 3)(9x - 1) = 0 |
Tìm x:
a)(x+2)^2-2(x+2)(x-5)=0
b)2x^2+3x-5=0
c)x+2√2x^2+2x^3=0
d)(3x-1)^2-4(x+5)^2=0
Bài 4: Tìm x, biết.
a) 4x(x - 7) - 4x2 = 56
b) 12x(3x - 2) - (4 - 6x) = 0
c) 4(x - 5) - (5 - x)2 = 0
d) x(x +1) - x(x - 3) = 0
e) - 6x + 8 = 0 f) 2 + 2x + = 0
bài 3: tìm x , biết:
a)(x+3).(2x-1)-(x-3).(x+1)=0
b)(x+4).(2x-3)-3.(x-2).(x+2)=0
c)x.(x-5).(x+5)-(x+2).(x2-2x+4)=17
bài 1 tìm x
a)6x^2-72x=0
b)-2x^4+16x=0
c)x(x-5)-(x-3)^2=0
d)(x-2)^3-(x-2)(x^2+2x+4)=0
Tìm x , Biết
a) (x-4) x - (x-3)^2=0
b) 3x-6 = x^2-16
c) (2x-3)^2 - 49=0
d) 2x (x-5) - 7 (5-x)=0